2014
DOI: 10.1016/j.stem.2013.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Analysis via Barcoding Reveals Diverse Growth and Differentiation of Transplanted Mouse and Human Mammary Stem Cells

Abstract: Cellular barcoding offers a powerful approach to characterize the growth and differentiation activity of large numbers of cotransplanted stem cells. Here, we describe a lentiviral genomic-barcoding and analysis strategy and its use to compare the clonal outputs of transplants of purified mouse and human basal mammary epithelial cells. We found that both sources of transplanted cells produced many bilineage mammary epithelial clones in primary recipients, although primary clones containing only one detectable m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(76 citation statements)
references
References 39 publications
4
72
0
Order By: Relevance
“…The recent development of cellular barcoding technology offers an alternative approach to investigate the diversity of differentiation potential, although this requires an intervening culture period. The transplantation of barcoded basal cells into cleared fat pads resulted in many bilineage cells within the primary outgrowths, compatible with the existence of a common stem cell (Nguyen et al 2014). …”
Section: Matters Arising In Lineage Tracing and Transplantation Studiesmentioning
confidence: 82%
“…The recent development of cellular barcoding technology offers an alternative approach to investigate the diversity of differentiation potential, although this requires an intervening culture period. The transplantation of barcoded basal cells into cleared fat pads resulted in many bilineage cells within the primary outgrowths, compatible with the existence of a common stem cell (Nguyen et al 2014). …”
Section: Matters Arising In Lineage Tracing and Transplantation Studiesmentioning
confidence: 82%
“…These epigenetic changes impact the biological activity of cells through their modification of transcriptional states and regulatory machinery, and the proportion of cells carrying these mutations is known to vary at the genetic level [12,13]. But, a method for determining the proportion of cells that carry these changes has never been demonstrated at the epigenetic level, even though it has been reported that a subset of the CpG sites vary their methylation level between 20% and 80% [8].…”
Section: Resultsmentioning
confidence: 99%
“…Our findings establish the normal human luminal epithelium as a distinct site of oxidative stress resistance in the presence of high intracellular ROS levels mediated by a unique enzymatic repertoire. These features distinguish LPs from BCs, which include very primitive bipotent cells with both luminal and myoepithelial differentiation abilities (24). The unique properties of the LPs include up-regulated levels and activity of SODs and their superoxide substrates, with an accompanying switch in mechanisms used to control ROS levels and promote cell survival in the presence of increased ROS levels.…”
Section: Discussionmentioning
confidence: 99%